Fuzzy TOPSIS method in the selection of Investment Boards by incorporating operational risks - Madi, Elissa Nadia; Md. Tap, Abu Osman (International Association of Engineers, 2011)
Multi Criteria Decision Making (MCDM) involves not only attributes that are precise or crisp, but also values that are not deterministic. Currently, Fuzzy TOPSIS presents a solution for decision makers when dealing with real world data that are usually multi attributes and involves a complex decision making process. In this work, an application of this method is demonstrated in the selection of Investment Boards by taking into account the operational risks involved.